DETEKSI REAL-TIME KONDISI BATERAI MENGGUNAKAN SISTEM MONITORING BERBASIS PERANGKAT BERGERAK - Kusumojakti, Mochamad Aqsha Pasalewa; Zaky, Umar (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
In this digital era, the need for real-time monitoring of battery conditions is increasing, especially in devices used in daily activities, such as motorized vehicles. This research is a mobile device-based battery condition monitoring system that detects voltage, current, temperature, and calculates State of Charge (SoC) and State of Health (SoH) in real-time. This system uses a 0–25V voltage sensor, an ACS712 current sensor, and a DHT22 temperature sensor controlled by a Wemos D1 R32 as a microcontroller. The sensor reading data will then be sent to the database and displayed in the Android application. System testing is carried out to test system functionality and read battery condition data. As a result, each sensor can run well and show results in accordance with the expected conditions. The reaction sensitivity of each sensor is also said to be quite good, this is proven when the ACS712 voltage and current sensor is not connected to the battery, it shows a condition value of 0, the same as the DHT22 temperature sensor which will produce a high value if the surrounding temperature is high and a low value if the surrounding temperature medium low.